An integrative model of consumers' intentions to purchase travel online - Amaro, Suzanne (2014)
Grounded in the Theory of Reasoned Action, the Theory of Planned Behaviour, the Technology Acceptance Model and on the Innovation Diffusions Theory, this study proposes and empirically tests an integrated model to explore which factors affect intentions to purchase travel online. Partial Least Squares Structural Equation Modelling was conducted to assess the hypotheses. The empirical results, obtained in a sample of 1732 Internet users, indicate that intentions to purchase travel online are mostly determined by attitude, compatibility and perceived risk. The theoretical contributions of this study and the practical implications are discussed and future research directions are detailed.